Methodology for assessing durability during wear of surface-hardened parts - Seidullayeva, О.Б.; Myrzaliyev, Д.С.; Ibragimova, З.А. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2024)
The article considers the method of durability during wear of surface-hardened parts. The increase in the strength of equipment is primarily due not only to an increase in the reliability of its main components, aggregates, connections and parts, but also to a reduction in costs and fuel consumption during production processes. The surface quality of machine parts includes both geometric characteristics and physical and mechanical properties. The study of the influence of the roughness of working surfaces on their wear resistance has shown that the minimum surface roughness does not always ensure its high wear resistance. The relationship between wear resistance and mechanical parameters is always determined experimentally. The coefficient p is proposed as a generalized parameter, to determine which it is necessary to consider the combined effect of the parameters specified in the article. Apparently, as a generalized criterion for evaluating the effectiveness of the developed carbonitration regime, a parameter controlled by the hardness and strength of the core of the product, as well as the hardness and strength of the surface-hardened layer, should be used. In turn, the article considers a number of ways to express the critical stress intensity coefficient through the tensile strength and yield strength. The research took into account the well-known results of scientific work carried out at the Department of Mechanics and Mechanical Engineering on state budget and grant topics in the field of mechanical engineering.